2010
DOI: 10.1002/fuce.200900153
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Testing in Dynamic Mode of HT‐PEMFC H3PO4/PBI Celtec‐P Based Membrane Electrode Assemblies for Micro‐CHP Applications

Abstract: High temperature proton exchange membrane fuel cells (HT‐PEMFC) have a promising market in micro‐combined heat and power (μ‐CHP) applications. Operating above 150 °C, they would better cope with return temperatures of typical heating systems than conventional PEMFCs and would allow simplification of system regulations dedicated to failure prevention.Single cell and 500 We HT‐PEMFC stack integrating Celtec P 1000 MEAs were fed with synthetic reformate and air and successfully operated at 160 °C under accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…http://repository.uwc.ac.za Moçotéguy et al [123] reported steady-state long term testing for a single cell and a 500 W stack with pure and simulated reformate fuel. They achieved 1105 and 658 h for the single cell and the stack, respectively.…”
Section: Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…http://repository.uwc.ac.za Moçotéguy et al [123] reported steady-state long term testing for a single cell and a 500 W stack with pure and simulated reformate fuel. They achieved 1105 and 658 h for the single cell and the stack, respectively.…”
Section: Degradationmentioning
confidence: 99%
“…Moçotéguy et al [123] studied the effect of using reformate fuel reporting a loss of 70e90% of the anode catalyst surface area due to the presence of CO. Moreover, carbon support corrosion and membrane oxidation were reported to be enhanced in HT-PEMs increasing the durability challenge [114].…”
Section: Degradationmentioning
confidence: 99%
“…Concerning PBI/phosphoric acid membrane based high temperature PEMFC, a number of durability studies have been performed on both single cells [16][17][18][19][20][21] and stacks [20,21]. Among the identified component failure mechanisms the oxidative degradation of polymer membranes is a key issue [3].…”
Section: Introductionmentioning
confidence: 99%
“…Bandlamudi et al [19] have studied the properties of 150 W PBI/H 3 PO 4 Gel-Based Polymer Electrolyte Membrane Fuel Cells under the Influence of Reformates. Stacks based on Celtec-P commercial high temperature membranes are also being tested [20]. Bonville et al [21] have studied the effect of scaling up (from 25 cm 2 to 300 cm 2 ) on the cell performance and properties using Ionomem corporations composite membrane based on PTFE, Nafion and phosphotungstic acid at 120…”
Section: Introductionmentioning
confidence: 99%